1987
DOI: 10.1128/aem.53.3.542-548.1987
|View full text |Cite
|
Sign up to set email alerts
|

Intergeneric protoplast fusion between Fusobacterium varium and Enterococcus faecium for enhancing dehydrodivanillin degradation

Abstract: Intergeneric protoplast fusion between Fusobacterium varium (Pcs Glu+) and Enterococcus faecium (Pcr Glu-) was performed under strictly anaerobic conditions to improve dehydrodivanillin (DDV) degradation. The fusion frequency obtained from the selective medium (Pc+ Glu-) was about 0.9 x 10-5 to 1.3 x 10-5. The seven fusants isolated were all gram-negative anaerobes with rod shapes like that of F. varium and with main phenotypical properties of cocci like those of E. faecium such as esculin and starch hydrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The protoplast fusion technique has been studied (4, 8-11, 16, 20) extensively as a means of genetic transfer or recombination. We have previously reported a successful intergeneric protoplast fusion system between Fusobacterium varium and Enterococcus faecium under anaerobic conditions for enhancing dehydrodivanillin (DDV) degradation (2,3). Our results suggested that genetic transformation and recombination can take place through protoplast fusion between bacterial strains that are distantly related taxonomically.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…The protoplast fusion technique has been studied (4, 8-11, 16, 20) extensively as a means of genetic transfer or recombination. We have previously reported a successful intergeneric protoplast fusion system between Fusobacterium varium and Enterococcus faecium under anaerobic conditions for enhancing dehydrodivanillin (DDV) degradation (2,3). Our results suggested that genetic transformation and recombination can take place through protoplast fusion between bacterial strains that are distantly related taxonomically.…”
mentioning
confidence: 73%
“…), kanamycin sulfate (Takeda Chemical Industries Co.), restriction enzyme PstI (Nippon Gene Co., Ltd), polyethylene glycol (PEG) 6000 and Congo red (Wako Pure Chemical Co.), API 20A test kit for the identification of anaerobes and API ZYM test kit for the assay of enzymatic activities (API System S.A., La Balme Les Grottes, 38390-Montalieu Vercieu, France). o-Carboxymethyl cellulose (CMC) samples were generously provided by Daiichi Kogyo Seiyaku Co. All the other reagents were the same as those described previously (2,3) and were commercial products of analytical grade.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene glycol (PEG)-induced cell fusion is one of the means to transfer DNA between bacterial cells, and numerous instances have been reported for intraspecific, interspecific, and intergeneric protoplast fusion (Akamatsu & Sekiguchi, 1983;Chen et al, 1986Chen et al, , 1987Cocconcelli et al, 1986;Baigorí et al, 1988;van der Lelie et al, 1988;van der Vossen et al, 1988;Gokhale & Deobagkar, 1989). The genetic materials used in these studies include either plasmids or chromosomal DNA.…”
Section: Introductionmentioning
confidence: 99%
“…into Bacillus subtilis were achieved. More recently, the successful use of intergeneric protoplast fusion to transfer genomic traits such as lignin degradation (6) and nitrogen fixation (36) in bacteria has been reported. The expression of cellulases in bacteria could be improved in both the quality and quantity of the desired enzyme as required by introducing various kinds of mutations into the relevant genes.…”
mentioning
confidence: 99%